Can nurses help improve self‐care of patients living with atrial fibrillation? A focus group study exploring patients' disease knowledge gaps - Tammy R. Toscos; Amanda Coupe; Shauna Wagner; Michelle Drouin; Amelia E. Roebuck; Carly N. Daley; Maria D. Carpenter; Michael J. Mirro (Wiley, 2020)
Abstract Aims To identify knowledge gaps and preferences for educational material to improve nurse-patient communication and self‐care. Design Using a mixed‐methods design, we conducted focus groups and quantitative surveys. Methods We conducted three focus groups with atrial fibrillation (AF) patients and support persons (N = 17 participants; 66 ± 16 years) at critical treatment junctures (recent diagnosis or medication switch). Patients and support persons were also surveyed on patient activation (self‐management skills and knowledge), medication adherence, AF knowledge and health literacy. Iterative thematic analysis was performed using focus group transcripts. Results Although most participants had adequate health literacy, most reported gaps in AF knowledge. Participants lacked disease‐related knowledge and were unsure how to manage health behaviours (e.g. diet and exercise). Few felt they received adequate education from their healthcare provider. Results emphasize the need for consistent information from nursing staff, in lay language, via both electronic and printed means.